Bullet magnet : britain's most highly decorated frontline soldier - Flynn, Mick. ([S.l.] : Weidenfeld & Nicolson, 2010)
Summer 2006, Afghanistan: an apparently deserted village, and a rapidly ticking clock...The relentless Taliban ambush which followed saw several British soldiers dead, two armoured vehicles destroyed - and Corporal of Horse Michael Flynn awarded an MC to go alongside his Conspicuous Gallantry Cross. Mick Flynn has never backed away from a challenge. From his uncompromising South Wales childhood - within a whisker, at one point, of Cardiff Prison - to the streets of Belfast, where he first learned the bitter realities of armed conflict, he's had no difficulty finding and facing trouble. Whether on the storm blasted Falklands cliff tops, where he witnessed the Sir Galahad going down in flames, or in the searing deserts of Iraq, where he and his crew pinned down an entire division of enemy tanks, he has carried the attack with a coolness that has earned him the respect of princes, generals and his fellow soldiers. Mick Flynn has seen action in every major British war zone of the past thirty years and still serves with the legendary Blues & Royals today. Bullet Magnet is his story - the story of an extraordinary modern warrior who mixes warmth and humour, and at times heartbreaking poignancy, with truly breathtaking fighting skills.